GSK3β-SCFFBXW7α mediated phosphorylation and ubiquitination of IRF1 are required for its transcription-dependent turnover. Issue 9 (11th March 2019) - Garvin, Alexander J; Khalaf, Ahmed H A; Rettino, Alessandro; Xicluna, Jerome; Butler, Laura; Morris, Joanna R; Heery, David M; Clarke, Nicole M
Abstract: IRF1 (Interferon Regulatory Factor-1) is the prototype of the IRF family of DNA binding transcription factors. IRF1 protein expression is regulated by transient up-regulation in response to external stimuli followed by rapid degradation via the ubiquitin-proteasome system. Here we report that DNA bound IRF1 turnover is promoted by GSK3β (Glycogen Synthase Kinase 3β) via phosphorylation of the T181 residue which generates a phosphodegron for the SCF (Skp-Cul-Fbox) ubiquitin E3-ligase receptor protein Fbxw7α (F-box/WD40 7). This regulated turnover is essential for IRF1 activity, as mutation of T181 results in an improperly stabilized protein that accumulates at target promoters but fails to induce RNA-Pol-II elongation and subsequent transcription of target genes. Consequently, the anti-proliferative activity of IRF1 is lost in cell lines expressing T181A mutant. Further, cell lines with dysfunctional Fbxw7 are less sensitive to IRF1 overexpression, suggesting an important co-activator function for this ligase complex. As T181 phosphorylation requires both DNA binding and RNA-Pol-II elongation, we propose that this event acts to clear 'spent' molecules of IRF1 from transcriptionally engaged target promoters.